Polyketide- and Terpenoid-Derived Metabolites Produced by a Marine-Derived Fungus, Peroneutypa sp. - de Amorim, Marcelo R.; Barbosa, Camila de S.; Paz, Tiago A.; Ióca, Laura P.; Nicácio, Karen J.; de Oliveira, Lucianne F. P.; Goulart, Mirian O.; Paulino, Julia M.; da Cruz, Mateus O. [UNESP]; Ferreira, Antonio G.; Furlan, Maysa [UNESP]; de Lira, Simone P.; et al. (American Chemical Society (ACS), 2023)
Bioassay-guided investigation of the EtOAc-soluble extract of a culture of the marine-derived fungus Peroneutypa sp. M16 led to the isolation of seven new polyketide- and terpenoid-derived metabolites (1, 2, 4-8), along with known polyketides (3, 9-13). Structures of compounds 1, 2, and 4-8 were established by analysis of spectroscopic data. Absolute configurations of compounds 1, 2, 4, 6, 7, and 8 were determined by the comparison of experimental ECD spectra with calculated CD data. Compound 5 exhibited moderate antiplasmodial activity against both chloroquine-sensitive and -resistant strains of Plasmodium falciparum.